2002
DOI: 10.1016/s0022-5347(05)65171-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of Contrast Enhanced Color Doppler Targeted Biopsy With Conventional Systematic Biopsy: Impact On Prostate Cancer Detection

Abstract: Contrast enhanced color Doppler targeted biopsy detected as many cancers as systematic biopsy with fewer than half the number of biopsy cores. Although an increase in cancer detection was achieved by combining targeted and systematic techniques in this screening population, contrast enhanced targeted biopsy alone is a reasonable approach for decreasing the number of biopsy cores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(42 citation statements)
references
References 19 publications
2
32
0
8
Order By: Relevance
“…Compared with Doppler imaging employed by most previous studies (7-9, 14), the CPS harmonic imaging used in this study recognizes and processes the unique nonlinear fundamental and higher order harmonic signals generated by the contrast agent, thus allowing for a significant increase in the specificity of contrast agent-to-tissue, even at low mechanical index power levels. Furthermore, grayscale CPS imaging is less affected by motion noise and blooming artifact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with Doppler imaging employed by most previous studies (7-9, 14), the CPS harmonic imaging used in this study recognizes and processes the unique nonlinear fundamental and higher order harmonic signals generated by the contrast agent, thus allowing for a significant increase in the specificity of contrast agent-to-tissue, even at low mechanical index power levels. Furthermore, grayscale CPS imaging is less affected by motion noise and blooming artifact.…”
Section: Discussionmentioning
confidence: 99%
“…With contrast-enhanced targeted biopsy, the prostate cancer detection rate can be improved with fewer cores (7-9). Also, another study found that contrast-enhanced ultrasonography was more sensitive in detecting higher grade tumors (10) and the author suggested that contrast-enhanced ultrasound might be helpful in grading the prostate cancer.…”
mentioning
confidence: 99%
“…One of the most important findings is that with CEUS the number of biopsies can be greatly reduced [20, 21] with a comparable cancer detection rate. Quantification techniques are now developed and introduced that have the potential to increase the accuracy of CEUS analysis and decrease the user dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Of 230 patients, PCa was detected in 69 patients (30%), with CB in 56 patients (24.4%), and with SB in 52 patients (22.6%). They concluded that the same detection rate can be obtained with less biopsies when CECD-guided biopsies are used [20]. In 2005, Pelzer et al performed a combined approach of CB and SB to investigate the impact on PCa detection.…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…[ 18 ] compared colour Doppler contrast-enhanced US targeted biopsy (CB) of the prostate using Levovist (Schering, Germany) with grey-scale ultrasound-guided systematic biopsy (SB). Two hundred and thirty male screening volunteers were included.…”
Section: Prostate Cancermentioning
confidence: 99%